On the wrong side of history - Israel, Latin America and the United States under a peripheral-realist perspective, 1949-2012 - Escudé, Carlos Andrés (2013)
This paper applies peripheral realist theory to the case of the long-term interstate relations between Israel and the Latin American countries. It attempts to understand the change in these relations, which began with full-fledged Latin American support for the establishment of the State of Israel, but deteriorated following the establishment of the US-Israeli alliance. It interprets the US-Israeli-Latin American triangle as a nonWaltzian hierarchical interstate structure, and suggests that the involution in IsraeliLatin American relations can largely be explained in terms of at least five intervening variables: Israel’s vulnerability; its special relationship between the United States and Israel after 1967; the establishment of full electoral democracies in Latin America after 1983; the region’s social structures, and class identity of the Latin American Jewry.